Trace Elements Investigations in the Serpentine-Kougarok Area, Seward Peninsula, Alaska - West, W. S.; Moxham, R. M. (Geological Survey (U.S.), 1949)
Report discussing the U.S. Geological Survey's investigation of radioactive materials in the Serpentine-Kougarok on the Seward Peninsula of Alaska.